Estudo de implantação de um sistema de estacionamento rotativo na região central da cidade de Campo Mourão-PR - Cassiano, Luciano Vieira (2014)
Investigations of issues related the management of traffic of vehicles constitute one of the largest field of study of Traffic Engineering. This study aimed to identity a supposedly poor use of occupation and availability of public parking of central area of Campo Mourão, Paraná. With the case study, propose a Project in order to restore the urban mobility for intermediate paid a rotating parking. Concluding that there is a low supply of vacancies in the central area of the city, paid project parking lots submitted for collection that were designed as a proposal of possible solution for balancing the supply and demand for parking.